Deficit Irrigation Technique to Improve Water Productivity of Avocado Grown on Mulched Sandy Soi - Mostafa Sokkar; Eslam Ahmed; Ahmed Ibrahim; Manal Mubarak; Mona Nosseir (Arab Universities Journal of Agricultural Sciences, 2022)
A field experiment was conducted in new reclaimed areas to improve avocado trees water productivity cultivated under deficit irrigation and mulching. The deficit irrigation treatments were 90, 80, 70, and 60% of reference evapotranspiration (ETo). Results revealed that The average water requirements during different avocado trees physiological growth stages were 613, 1509, 1755, 1391, and 632 m3 /fed for flowering to end of fruit set, fruit set to approximately 50% of the expected market fruit size, during the fruit growth stage, during the fruit ripening stage, and during the flower bud formation stage, respectively. These values represent approximately 10.4%, 25.6%, 29.7%, 23.6%, and 10.7% of the total yearly water requirement. The averages irrigation frequency were 2.45, 2.61, 2.72, 2.87, and 3.91day for 100, 90, 80, 70 and 60% ETo treatments, respectively. The highest crop water productivity value of 1.24 kg/m3 water was attained at 70% ETo followed by 1.18 kg/m3 water at 80% ETo while the least crop water productivity (1.06 kg/m3 water) was realized at 100% ETo. The crop water requirement of 5110 m3 /fed/year with high irrigation frequency is recommended for mulched sandy soil cultivated with avocado trees.